2002
DOI: 10.1002/1099-0690(200210)2002:20<3447::aid-ejoc3447>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomerism and Ring-Chain Tautomerism in 1-Hydroxy-2,3-dihydro-1H-pyrazolo[1,2-a]pyridazine-5,8-diones and 1-Hydroxy- and 1-Amino-2,3-dihydro-1H-pyrazolo[1,2-b]phthalazine-5,10-diones

Abstract: 1‐Hydroxy‐2,3‐dihydro‐1H‐pyrazolo[1,2‐a]pyridazine‐5,8diones and 1‐hydroxy‐ and 1‐amino‐2,3‐dihydro‐1H‐pyrazolo[1,2‐b]phthalazine‐5,10‐diones were synthesized and their structures studied by NMR and MS methods. All compounds exist in similar cyclic forms in solution, except for 1hydroxy‐1‐methyl‐2,3‐dihydro‐1H‐pyrazolo[1,2‐a]pyridazine‐5,8‐dione, which displays ring‐chain tautomerism in CDCl3 solution. The corresponding 3‐methyl‐substituted derivatives exhibit a typical cis/trans isomerism as a result of laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Ring-chain tautomerization has been shown to occur in a number of heterocyclic compounds. 10,[12][13][14][15][16][17][18][19][20] The tautomerism results from an interconversion of the chain and the ring isomers. For compounds 7-12, the two enantiomers (S-M) and (R-P) (see Fig.…”
Section: Stereoselectivity (Diastereoselectivity) In Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ring-chain tautomerization has been shown to occur in a number of heterocyclic compounds. 10,[12][13][14][15][16][17][18][19][20] The tautomerism results from an interconversion of the chain and the ring isomers. For compounds 7-12, the two enantiomers (S-M) and (R-P) (see Fig.…”
Section: Stereoselectivity (Diastereoselectivity) In Reductionmentioning
confidence: 99%
“…23,24 However, such an intermediate was not observed in the NMR time scale in CDCl 3 . Taking the NMR spectra in d 6 -DMSO in the absence or presence of trifluoroacetic acid-d or pyridine-d 5 , which could stabilize the aldehyde intermediate 10,12 did not exhibit its existence as well. With the aim of trapping the aldehyde intermediate as an imine, the compound 10 was treated with benzyl amine in toluene under reflux for one day as has been described in Ref.…”
Section: Stereoselectivity (Diastereoselectivity) In Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with monosubstituted hydrazines in organocatalytic asymmetric synthesis, disubstituted hydrazines were also explored by several groups [7273]. In 2007, Jørgensen et al reported that the organocatalyzed asymmetric aza-Michael addition of hydrazones to cyclic enones had been achieved in good yield and stereoselectivity [74].…”
Section: Introductionmentioning
confidence: 99%